2014
DOI: 10.15680/ijirset.2014.0308078
|View full text |Cite
|
Sign up to set email alerts
|

. Comparative Study on Pectin Yield According To the State of the Orange Peels and Acids Used

Abstract: ABSTRACT:Moroccan Orange peels are a promising commercial source of pectin. Their massive industrialization generates a huge amount of solid waste. This work aims to develop a new valorizing reuse way of this solid waste by developing the extraction process of value-added products such as pectin from orange peels, which is the waste of orange juice processing industry. In this context, we evaluated the yield of pectin according to the state of the substrate and the acids used. Results obtained show that the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In previous works [ 44 ], we have used two batches of ground citrus peels. The first batch was washed with water in order to remove impurities, dried and ground for pectin extraction, while essential oil were extracted from the second one (vapodistillation).…”
Section: Methodsmentioning
confidence: 99%
“…In previous works [ 44 ], we have used two batches of ground citrus peels. The first batch was washed with water in order to remove impurities, dried and ground for pectin extraction, while essential oil were extracted from the second one (vapodistillation).…”
Section: Methodsmentioning
confidence: 99%
“…There are several reports on pectin isolation from citrus peel including conventional acid extractions (Srivastava and Malviya, 2011b) and MW-assisted processes (Boukroufa et al, 2015;Guo et al, 2012;Hosseini et al, 2016;Prakash Maran et al, 2013). The effects of the mineral (HCl, H 2 SO 4 ) and organic (citric, acetic) acids used to promote pectin extraction have also been explored (Sayah et al, 2014). While MW extraction has proved to be the greenest approach with extraction times ranging from 3 to 20 min, and yields from 15 to 30 %(w/w) (Boukroufa et al, 2015;Guo et al, 2012;Hosseini et al, 2016;Prakash Maran et al, 2013), the use of organic acids, such as citric acid, is more desirable because its involves less toxic and less hazardous operation conditions.…”
Section: Citrus Waste-based Biorefining: Pectin Mw Assisted Extractiomentioning
confidence: 99%
“…13, No. 1 (2020) Sayah et al (2014) found that the pectin yield of orange peel extraction using citric acid (38.52 %) was slightly higher than that of HCl (35.34 %). Castillo-Israel et al (2015) also found that citric acid (pH of 1.7) with the extraction time of 1-2 h was able to give the higher yield for pectin extraction from unripe banana peel than the use of HCl (pH of 1.5).…”
mentioning
confidence: 99%